Removal of Methyl Orange in Aqueous Medium using ZnO/Bentonite as Semiconductor by Photocatalytic Process - Priatna, Satria Jaya; Yuliana, Ayu; Zulkarnain; Melwita, Elda; Arsyad, Fitri Suryani; Mohadi, Risfidian (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Pillarization of bentonites (from East Java) with ZnO semiconductors has been synthesized using co-precipitation methods into a ZnO/Bentonite composite and applied as a catalyst in a photocatalytic process to remove Methyl Orange (MO) dyes. The optimum pH condition of MO dyes is at pH 2 with a degradation rate of 22.91% (from 15 mg/L to 11.523 mg/L). The optimum ZnO/Bentonite catalyst weight condition is 200 mg, with a degradation rate of 29.11% (from 15 mg/L to 10.596 mg/L). The optimum time condition for UV lamp irradiation is 60 minutes, with a degradation rate of 64.92% (from 15 mg/L to 5.244 mg/L). The kinetics of MO photocatalytic reaction using ZnO/Bentonite catalyst follows the pseudo-first-order Langmuir Hinshelwood-Santosa kinetic model with photocatalytic reaction rate constant (k1) of 0.014 and photocatalytic equilibrium constant (K) of 0.012.